The Potential of ChatGPT as a Substitute for Human Teachers: Insights from Tunisian EFL Learners' Perspectives - Najeh, Leila (Magister Pendidikan Bahasa Inggris Universitas Jambi, 2025)
Artificial intelligence (AI) has brought about various language robots, with ChatGPT being among the most sophisticated due to its human-like linguistic capabilities and adaptability. This raises the idea of using ChatGPT in foreign language learning. Starting from the premise that positions ChatGPT as a mediator between language and learner, functioning as a “ghost teacher” offering a peaceful and secure learning space, this study explores the attitudes of Tunisian students of English towards ChatGPT as a “Foreign Language Teacher” and digital assistant. Forty-five third-year English students at Tunisian universities completed a Likert-scale questionnaire consisting of thirty-one items covering phonology, morphology, syntax, semantics, and pragmatics. A scale ranging from 'Strongly Disagree' to 'Strongly Agree' was used to assess their attitudes toward integrating ChatGPT in language learning effectively and meaningfully. Results indicate generally positive attitudes toward using ChatGPT, particularly in aspects like syntax, phonology, and morphology. However, learners show hesitation regarding its usefulness in pragmatics and semantics, where AI may struggle with deeper, context-sensitive language levels and cultural nuances. These attitudes are shaped by several factors, especially students' technological familiarity and the structure of the education system. Learners with regular exposure to digital tools and online environments tend to be more receptive to AI integration. In contrast, those from rural or under-resourced areas often express skepticism due to limited access and training. Moreover, the nature of the academic system, whether teacher–centered or learner-centered, influences perceptions of AI's usefulness in education and its potential role in personalized learning.